IMPLEMENTASI PENYUSUNAN PENELITIAN TINDAKAN KELAS (PTK) DALAM BENTUK ARTIKEL UNTUK PENGUATAN KINERJA GURU - Agustina, Lady; sudahri, sudahri; Dewi, Ilanka Cahya (FKIP Universitas Wisnuwardhana, 2024)
In essence, teachers' duties are not limited to just teaching and being able to deliver learning material well, but teachers are also required to continuously develop, adopt various innovations and creations, study, observe and analyze many things in the world of education. Teachers determine the quality of students (output), and of course, the quality of the nation's education. If the teacher understands the task, the teacher will always improve his learning until he finds the best learning system. Efforts to improve the quality of learning actually contain elements of PTK. The aim of action research is to improve practice in the world of education, researchers study their own problems that occur in the classroom or problems in schools or educational environments. The PkM activity approach method to support efforts to improve teacher performance and quality in the classroom learning process by compiling Class Action Research (PTK) can be realized through: implementing the preparation of Class Action Research (PTK) in the form of articles to strengthen teacher performance. The implementation plan for PkM activities consists of four stages, namely (1) implementation coordination, (2) program socialization, (3) implementation, and (4) evaluation of activity results